2019
DOI: 10.1186/s12936-019-2672-7
|View full text |Cite
|
Sign up to set email alerts
|

Community perspectives on treating asymptomatic infections for malaria elimination in The Gambia

Abstract: Background Innovative and cost-effective strategies that clear asymptomatic malaria infections are required to reach malaria elimination goals, but remain a challenge. This mixed methods study explored people’s attitudes towards the reactive treatment of compound contacts of malaria cases with a 3-day course of dihydroartemisinin-piperaquine (DHAP), the socio-cultural representations of asymptomatic infections, and more specifically their treatment. Methods Prior to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
4
18
0
1
Order By: Relevance
“…3 and Box 1. This work further demonstrates the value of rapid ethnographic assessments to inform community engagement [12,18] and adds to previous research on motivations and barriers to MDA for malaria on Hispaniola [19] and elsewhere [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 53%
“…3 and Box 1. This work further demonstrates the value of rapid ethnographic assessments to inform community engagement [12,18] and adds to previous research on motivations and barriers to MDA for malaria on Hispaniola [19] and elsewhere [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 53%
“…In the study setting, the communities had a long political and engagement history with the implementing institution wherein trust in their role was mainly based on their reputation for providing good health care against the backdrop of a limited health system 44 , 45 . VHWs who often collaborated with the MRCG in projects were considered as key stakeholders for further facilitating treatment acceptance and adherence 37 , 46 . Nonetheless, community’s trust in the VHWs and their socio-political leverage was fundamentally dependent on the VHWs perceived capacity to provide curative services for malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason for this high rate of asymptomatic P. vivax infections is unknown, it is probably associated with the unique biology of P. vivax that includes a fast acquisition of clinical immunity as compared with P. falciparum [47]. It is particularly relevant because in different epidemiological settings there are perspectives on treating asymptomatic infections for malaria elimination [48]. In the study area, the results demonstrated that, in general, multiple molecular targets (i.e., ribosomal plus non-ribosomal) did not increase sensitivity to detect subclinical malaria infections.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, WHO recommends that the use of NAATs be considered only for epidemiological research or surveys mapping submicroscopic infections in low transmission areas [54]. Innovative and cost-effective strategies that identify the real burden of malaria infections (those detected by qPCR) are required to reach malaria elimination goals, but remain a challenge [48].…”
Section: Discussionmentioning
confidence: 99%